Transformasi Pembelajaran Bahasa Indonesia melalui Project Based Learning: Analisis Kemampuan Belajar Siswa di SDN 1 Bumiayu - Yuriananta, Renda; Angelia, Cindy Aprilia; Soliha, Lailatus; Hakim, M. Keivin Al; Wulandari, Nabila Tri; Laili, Vina Nur (University of Brawijaya, 2026)
Indonesian language instruction in primary schools needs to be geared toward active, contextual, and meaningful learning experiences, particularly within the implementation of the *Kurikulum Merdeka* (Independent Curriculum), which emphasizes student-centered learning. This study aims to analyze the transformation of Indonesian language instruction through the application of Project-Based Learning (PjBL) at SDN 1 Bumiayu. A descriptive qualitative approach was employed, with teachers from SDN 1 Bumiayu serving as the primary informants. Data were collected through semi-structured interviews, field notes, and instructional documentation. Data analysis involved data reduction, data presentation, and conclusion drawing. The results indicate that lesson planning was conducted through the collaborative development of teaching modules within the school cluster, tailoring practical activities to the characteristics of the students' environment. The implementation of PjBL provided opportunities for students to learn through practice, environmental observation, and hands-on experiences, such as observing plants and utilizing simple learning aids. A learning challenge arose from the students' predominant use of Madurese in daily communication; consequently, teachers fostered the use of Indonesian in the classroom through correction and guidance. Learning evaluation emphasized not only summative assessment but also diagnostic assessment, active participation, interaction, collaboration, and problem-solving skills. The study concludes that PjBL has the potential to transform Indonesian language instruction into a more contextual, active, and meaningful process when supported by adaptive planning, simple learning aids, communicative language management, and process-oriented assessment.